Prevention of mental disorder recurrence using patient education program (PEP) therapy and family Psycho-education (FPE) therapy - Rachmawati, Umi; Islamiyah, Islamiyah; Firman, Firman; Yusnayanti, Cici (Universitas Muslim Indonesia, 2021)
People with severe mental disorders or schizophrenia often have recurrence episodes. If the clients have undergone treatment in the hospital, the treatment process can continue at home. However, clients are often unable to stay at home for a long time and experience recurrence episodes. This study aimed to find out the effect of giving Patient Education Program (PEP) therapy and Family Psycho-Education (FPE) therapy on reducing recurrence of mental disorders. This study was a quantitative study using a quasi-experimental design pre and post-test nonequivalent control group. The results of the study using the Paired T-test in the intervention group had different mean scores of mental disorders recurrence before and after giving PEP and FPE therapy with a p-value of 0.000 (p less than a; 0.005). In addition, in the control group using the independent T-test, the results showed no difference in the mean score of mental disorders recurrence before and after giving PEP therapy with a p-value of 0.604 (p greater than a; 0.005). Giving PEP therapy and FPE therapy to people with mental disorders in the community impacts reducing symptoms of recurrence so that it can be used as an alternative solution to mental health problems in community